Tuhan Dalam Lintasan Sejarah Filsafat Barat - Saidul Amin; Ayu Rustriana Rusli (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The purpose of writing this article is to discuss the nature of God, or demiurge – creator and designer of the cosmos, whom a venerable subject in philosophy and natural theology. This paper aims to explore the concept of God in the thought of Western Philosophy. The understanding of God in the East is different from the West. East is rich with mystical life, revealing the divine realm through inner experience. While in the West, reason has always been a command and a tool to meet the